A case of acute epiglottitis caused by Haemophilus influenzae type a in an adult. Issue 3 (September 2014) - Cerqueira, Ashley M.; Tsang, Raymond S. W.; Jamieson, Frances B.; Ulanova, Marina
Abstract : Introduction: Prior to the introduction of a paediatric conjugate vaccine in the early 1990s, Haemophilus influenzae serotype b (Hib) was a major cause of childhood meningitis and pneumonia. Since becoming part of national immunization programmes, the Hib conjugate vaccine has been very successful in preventing invasive Hib disease worldwide. However, in the post‐Hib vaccine era, the emergence of invasive disease caused by non‐type b H. influenzae has been reported from several countries. Previous studies by our group found an increased incidence of invasive disease caused by H. influenzae serotype a in Northwestern Ontario, Canada, during 2002–2011. Most of the cases of invasive H. influenzae type a disease occurred in young children. Case presentation: Our continued surveillance identified a case of epiglottitis caused by H. influenzae type a in a 65‐year old woman. This life‐threatening condition was historically associated with invasive Hib disease in young children but had not previously been reported in association with H. influenzae type a. We describe the clinical presentation of this case as well as characteristics of the H. influenzae type a isolate. Conclusion: Our findings stress the importance of continued surveillance of H. influenzae in the post Hib‐vaccine era, and point to the significance of H. influenzae type a as a cause of severe invasive disease in countries with a universal paediatric anti‐Hib immunization programme.